Perkembangan Berbicara pada Anak Usia Dini Ditinjau dari Lingkungan Urban (Perkotaan) dan Rural (Pedesaan) - Saputri, Dina Wulan; Masruroh, Umy; Raihana, Raihana (UIR PRESS, 2026)
Speaking development is an important aspect of early childhood language development that supports children’s cognitive, social, and emotional growth. Children’s speaking abilities are strongly influenced by the environment in which they grow and develop, particularly urban (rural village-based) and rural (urban city-based) environments, which have different social characteristics and interaction patterns. This study aims to examine early childhood speaking development from the perspective of urban and rural environments. The research method employed is a literature review by analyzing national scientific journal articles related to early childhood speaking development, environmental influences, and parental roles. The data were analyzed using a descriptive-analytical approach by categorizing research findings into key thematic areas. The results indicate that children growing up in rural village environments tend to demonstrate greater speaking confidence and stronger contextual communication skills due to intensive and natural social interactions. In contrast, children in urban city environments tend to exhibit broader vocabulary mastery and more structured language use as a result of formal education and learning media. Therefore, the environment plays a significant role in shaping early childhood speaking development, and language stimulation should be adapted to the characteristics of the child’s living environment.